2020
DOI: 10.18632/aging.202246
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-2 attenuates hepatic ischemia-reperfusion injury by activating PI3K/Akt signaling

Abstract: Hepatic ischemia-reperfusion injury (IRI) remains a common complication during liver transplantation (LT), partial hepatectomy and hemorrhagic shock in patients. As a member of the G protein-coupled receptors adaptors, ARRB2 has been reported to be involved in a variety of physiological and pathological processes. However, whether β-arrestin-2 affects the pathogenesis of hepatic IRI remains unknown. The goal of the present study was to determine whether ARRB2 protects against hepatic IR injury and elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In different ischemia-reperfusion injury mouse models applied on hepatic and cardiac tissues, increased levels of p-PI3K, p-Akt have been recorded, indicating that I/R may activate the PI3K/Akt signaling pathway to initiate tissue repair following injury ( Zhang et al, 2014 ; Thokala et al, 2017 ). Targeting PI3K/Akt signaling pathway by different pharmacological therapies as a potential protective pathway against I/R injury has attracted great attention in many studies ( Yapca et al, 2013 ; Guan et al, 2020 ; Chen et al, 2021 ). In the current study, Western blot analysis showed significant upregulation in PI3K/Akt/mTOR expression in pancreatic tissue after nicorandil injection as a single treatment or combined with preconditioned MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In different ischemia-reperfusion injury mouse models applied on hepatic and cardiac tissues, increased levels of p-PI3K, p-Akt have been recorded, indicating that I/R may activate the PI3K/Akt signaling pathway to initiate tissue repair following injury ( Zhang et al, 2014 ; Thokala et al, 2017 ). Targeting PI3K/Akt signaling pathway by different pharmacological therapies as a potential protective pathway against I/R injury has attracted great attention in many studies ( Yapca et al, 2013 ; Guan et al, 2020 ; Chen et al, 2021 ). In the current study, Western blot analysis showed significant upregulation in PI3K/Akt/mTOR expression in pancreatic tissue after nicorandil injection as a single treatment or combined with preconditioned MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research has largely focused on the molecular targets and their mediated signaling pathways in HIRI. For example, SET8 alleviates mouse HIRI by inhibiting the microtubule affinity-regulating kinase 4 ( MARK4 )/nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain containing 3 ( NLRP3 ) inflammasome pathway ( 34 ), and ARRB2 alleviates HIRI by activating the phosphatidylinositol 3 kinase ( PI3K )/protein kinaseB ( AKT ) signaling pathway ( 35 ). Through a transcriptome analysis, our research identified the 6 key molecules closely related to HIRI, and successfully constructed the RF model of HIRI; in addition, we also successfully established a lncRNA-miRNA-mRNA network using a variety of bioinformatics analysis tools.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also shown that β-arrestins are involved in cell proliferation, apoptosis, and differentiation by mediating the Akt phosphorylation response to extensive stimulation in different cell types (42,43). Furthermore, PI3K-Akt signaling has been shown to play a central role in Arrb2medited cell protection (44,45). Therefore, we tested whether PI3K-Akt pathway is the downstream signaling mediator of the Arrb2-induced anti-apoptotic and proproliferation effects in TGCT.…”
Section: (C) Heatmap Of the Differentially Expressed Mrna Patterns In Tgct Versus Oa Synovitis The Relative Expression Is Indicated By Comentioning
confidence: 94%